Analysis of News and Feature Articles Using Corder Error Analysis in the Development of a Systematic Lesson, Guide, and Instruction in Journalism (SAGIP) - DONASCO, MARY JOY (International Journal of Arts, Sciences and Education, 2025)
The school newspaper serves as the voice of the students, but the clarity of the message may be affected by different writing errors. Using quantitative content analysis and developmental methods, the news and feature writings of 65 students from the Special Program in Journalism of T’boli National High School were analyzed. This study aims to assess the skills of student journalists in writing news and feature articles for school publication and to identify areas of their writing that needs improvement. The analysis showed a higher level of errors in news writing, particularly in syntactical and orthographical aspects. While the students demonstrated adequate skills in organization and content, improvement is still needed in vocabulary, writing style, and language use to enhance the quality of their writing. In writing features, students showed moderate ability in selecting the right words and organization but lacked in idea expression, adherence to proper style, and correct language use. It was found that students were better at writing news than feature articles. The study recommends the use of Systematic Lessons, Guides, and Instruction in Journalism (SAGIP), as supplementary instructional material that can be suitable for training for the campus journalists, though some aspects can still be improved to make it more effective in strengthening writing skills.